PENGARUH PEMBERIAN KREDIT DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Izaac Lukas Dominggus Lawalata (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of this study is to analyze the effect of credit and Non Performing Loan (NPL) on the profitability of conventional commercial banks listed on the Indonesia Stock Exchange. The analytical method used is quantitative associative analysis method by using multiple linear regression analysis, classical assumption test, coefficient of determination test and partial test. This research is conducted at Indonesia Stock Exchange (BEI). The object of this research is banking companies. This study focuses on conventional commercial banks listed on the Indonesia Stock Exchange, where the authors want to know about the effect of lending and Non Performing Loan (NPL) on the profitability of conventional commercial banks. So hopefully the authors can draw conclusions and provide suggestions that will be a consideration for a conventional commercial bank company in Indonesia Stock Exchange. The results showed that the variabelpemberian credit positive and significant impact on profitability and Non Performing Loan (NPL) have a negative and significant impact on profitability in conventional commercial banks listed on the Indonesia Stock Exchange.